(3GdPNjQI aj eMGSf Cgd GdLRjQIs - (3Ydj Hf HSGe GdTfJQjfj GdCfOdSj, CHh GdMSf,J (B542 (3g` s ((3CMeO Hf GdMGL Ydj Hf GdMGL CHj GdbGSe eMeO GHf ShOI GdCfOdSjs)
(3ChdgG (B:s
(3Ghdg eHJhQ hHYO KdGK hQbGJ jHOC aU aj PcQ GdhRGJjf GdcGJH CHj YHOGdQMef Hf WGgQ s
(3BNQgG (B:s
(3Je GdbSe GdKGdK ef cJGH GdPNjQI s
(3GdbFe GdKGdK ef fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B43s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B339 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B579 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B184 s
Keywords: (3GdJGQjNs